Universal System of Indicators for Assessing the Activities of Customs Authorities - BOBROVA, Anna Vladimirovna; GARIPOV, Robert Il'izarevich (Journal of Advanced Research in Law and Economics, 2019)
The subject of our research is the system of indicators for assessing the performance of regional customs directorates and customs offices, and for comparative analysis of the performance results of customs authorities. The purpose of the research is to create a universal system of indicators for regional and local customs authorities. The main method of research is system analysis, which allows us to formulate principles and determine methods of building a universal system of indicators. We also used weights, vertical analysis of indicators, modeling of the criteria for assessing the activities of customs authorities, comparative analysis, induction, approbation, ranking, and mathematical methods in our work. We show that the four groups of current indicators are not linked into a single system, they also duplicate each other, are excessively detailed, and have signs of intra-departmental regulation. We noted difficulties in implementing indicators and contradictions in their calculation methodology. We revealed premises for forming a universal system of indicators to assess the activities of customs authorities. We suggest a dual-purpose system of indicators to solve the issues we noted: from the perspective of the participants of foreign economic activities and customs authorities, the system was brought to the applied level and tested using data from acting customs authorities. We proposed a methodology for forming current, key, two-level, and final indicators for each customs authority. The results of our research can be useful to government bodies, participants of foreign economic activities, and researchers in the field of customs affairs.